THE DEVELOPMENT OF SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS (STEM)-BASED MATHEMATICS TEACHING MATERIALS TO INCREASE MATHEMATICAL CONNECTION ABILITY - M. A. Niam; M. Asikin (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This research is development research that aims to develop mathematics teaching materials related to Science, Technology, Engineering, and Mathematics (STEM). This research uses the stages of Research and Development, including problem and data collection, product design, design validation, product test (practicality test), trial test (pretest and posttest), and final product. The results show that teaching materials are valid, practical, and effective to increase mathematical connection ability. The results of the test indicate that teaching materials are valid to use in learning with a percentage of 94.42%. The practicality test results show that teaching materials are easily practised by students, with a percentage of 87.47%. The analysis of the results of the pretest and posttest showed that there was an effective increase in the mathematical connection ability with the n-gain test results of 0.628 on the medium criteria. Thus, mathematics teaching materials in this research can be used in learning, and the copyright was submitted by the electronic intellectual wealth General Directory.Abstract:Penelitian ini merupakan penelitian pengembangan yang bertujuan untuk mengembangkan bahan ajar matematika yang berhubungan dengan Science, Technology, Engineering, and Mathematics (STEM). Penelitian ini menggunakan tahapan penelitian dan pengembangan, yaitu masalah dan pengumpulan data, desain produk, validasi desain, uji produk (tes kepraktisan), uji coba (pretest dan posttest), dan produk akhir. Hasil penelitian menunjukkan bahwa bahan ajar tersebut valid, praktis, dan efektif untuk meningkatkan kemampuan koneksi matematis. Hasil tes menunjukkan bahwa bahan ajar valid untuk digunakan dalam pembelajaran dengan persentase 94,42%. Hasil tes kepraktisan menunjukkan bahwa bahan ajar mudah digunakan oleh siswa, dengan persentase 87,47%. Analisis hasil pretest dan posttest menunjukkan bahwa ada peningkatan yang efektif dalam kemampuan koneksi matematis dengan hasil tes n-gain dari 0,628 pada kriteria medium. Dengan demikian, materi pengajaran matematika dalam penelitian ini dapat digunakan dalam pembelajaran, dan hak cipta disampaikan oleh kekayaan intelektual elektronik direktori umum.